Patient preferences and priorities for haemophilia gene therapy in the US: A discrete choice experiment. Issue 5 (26th July 2021) - Witkop, Michelle; Morgan, George; O'Hara, Jamie; Recht, Michael; Buckner, Tyler W.; Nugent, Diane; Curtis, Randall; O'Mahony, Brian; Skinner, Mark W.; Mulhern, Brendan; Cawson, Matthew; Ali, Talaha M.; et al.
Abstract: Introduction: Gene therapy has shown promise in clinical trials for patients with haemophilia, but patient preference studies have focused on factor replacement treatments. Aim: We conducted a discrete choice experiment (DCE) to investigate the relative importance and differential preferences patients provide for gene therapy attributes. Methods: We surveyed male adults with haemophilia in the United States recruited from patient panels including the National Hemophilia Foundation Community Voices in Research platform using an online survey over 4 months in 2020/21. Participants indicated preferences for gene therapy attributes including dosing frequency/durability, effect on annual bleeding, uncertainty related to side effects, impact on daily activities, impact on mental health, and post‐treatment requirements. The relative importance of each attribute was analysed overall and for subgroups based on haemophilia type and severity. Results: A total of 183 males with haemophilia A (n = 120) or B (n = 63) were included. Half (47%) had severe haemophilia; most (75%) were White. Overall, participants gave effect on bleeding rate the greatest relative importance (31%), followed by dose frequency/durability (26%), uncertainty regarding safety issues (17%), and impact on daily activities (11%). Dose frequency/durability had the greatest importance for those with haemophilia B (35%). Conclusion: People with haemophilia prioritised reduced bleeding and treatment burden; the former was more important in haemophilia A and the latter in haemophilia B, followed by safety and impact on daily life in this DCE of gene therapy attributes. These findings and differences can inform clinical and health policy decisions to improve health equity for people with haemophilia.